UPAYA MENINGKATKAN PARTISIPASI ANAK REMAJA DALAM KEGIATAN SEKAMI MELALUI PENDEKATAN KATEKESE DI PAROKI St. ALFONSUS MARIA DE LIGUORI - Paulina Ros Narek; Agnes Oda Nimo Kian Boyang; Agustina Bulu Daton (Adiba Aisha Amira, 2026)
The participation of adolescents in the activities of the Pontifical Missionary Union of Children and Adolescents (SEKAMI) is a vital component of the faith formation of the Church’s younger generation. However, the low level of adolescent involvement in SEKAMI activities at St. Alphonsus Maria de Liguori Parish presents a pastoral challenge that requires attention. This Community Service activity aims to increase adolescent participation through a catechetical approach that is dialogical, participatory, creative, and contextual. The method used is participatory formation through a catechetical approach carried out in three stages: planning, implementation, and evaluation. The activities were carried out by students from Group VII of the Catholic Religious Education (PAK) course at the STP Reinha Larantuka Parish, targeting adolescents participating in SEKAMI activities at St. Alphonsus Maria de Liguori Parish. The activities included communal prayer, spiritual animation, presentation of materials, faith sharing, interactive discussions, educational games, communal reflection, and a commitment to active involvement. The results of the activity showed that the catechetical approach was able to increase enthusiasm, faith awareness, and active involvement of adolescents in SEKAMI activities. This approach proved effective as a pastoral tool in fostering adolescent participation in church life.